New Product Development Strategy of HEIMA Supply - Praditya, Patricius; Dellyana, Dina (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. In order to survive in a fast-paced fashion industry, a company must be able to listen to what their customers desired. Customers’ demand for a desirable will always changing, and thus a company must be able to keep up with the ever-changing demands. HEIMA is a fashion industry, which focuses on bags. Established in 2016, HEIMA aims to become a leader in Indonesia’s bag-maker industry. Quality and consistency is what they are holding high. But after launching its first product, HEIMA realize that the plan they had built at the beginning did not go as planned. The sales was low because the product did not meet the targeted markets’ expectation. Buyer persona analysis and Pearson’s New Product Development Process are the methods believed to be the answer to find the right product for the suitable customers. This research uses a qualitative research. By interviewing 20 people, which are chosen by using a purposive sampling, the researcher will then ask the respondents about the product they desired. The outcome of this research will be the researcher find the product that is desired by the customers, what personas suit the product, the marketing strategy, business analysis, and the acceptance of the newly developed product.Keyword: New Product Development Strategy; Buyer Persona Analysis; Fashion Industry